2017
DOI: 10.14814/phy2.13220
|View full text |Cite
|
Sign up to set email alerts
|

New indices from microneurography to investigate the arterial baroreflex

Abstract: Baroreflex‐mediated changes in heart rate and vascular resistance in response to variations in blood pressure are critical to maintain homeostasis. We aimed to develop time domain analysis methods to complement existing cross‐spectral techniques in the investigation of the vascular resistance baroreflex response to orthostatic stress. A secondary goal was to apply these methods to distinguish between levels of orthostatic tolerance using baseline data. Eleven healthy, normotensive males participated in a grade… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…Furthermore, the sensitivity of this intricate feedback mechanism increases during progressive LBNP-induced central hypovolemia as reflected by an elevated coherence between arterial pressure and sympathetic nerve activity (67,77). Laurin et al (217) quantified these interaction bursts at 0.1 Hz (Mayer waves) between MSNA and blood pressure changes during progressive steps of LBNP up to Ϫ60 mmHg in young, healthy subjects. Two new parameters for assessing the sympathetic nervous interaction with diastolic blood pressure at the level of the neuromuscular interface were quantified: stimulus time, defined as the time from the steepest drop in DBP to the first increase in MSNA; and response time, defined as time from the last bust of MSNA to the end of the DBP pulse response.…”
Section: Autonomic System and Lbnpmentioning
confidence: 99%
“…Furthermore, the sensitivity of this intricate feedback mechanism increases during progressive LBNP-induced central hypovolemia as reflected by an elevated coherence between arterial pressure and sympathetic nerve activity (67,77). Laurin et al (217) quantified these interaction bursts at 0.1 Hz (Mayer waves) between MSNA and blood pressure changes during progressive steps of LBNP up to Ϫ60 mmHg in young, healthy subjects. Two new parameters for assessing the sympathetic nervous interaction with diastolic blood pressure at the level of the neuromuscular interface were quantified: stimulus time, defined as the time from the steepest drop in DBP to the first increase in MSNA; and response time, defined as time from the last bust of MSNA to the end of the DBP pulse response.…”
Section: Autonomic System and Lbnpmentioning
confidence: 99%
“…Figure 2C shows the neurogram from the MSNA signal. Depolarizations of the sympathetic fibers that result in bursts can be observed ( Schreiber and Schmitz, 2000 ; Park et al, 2018 ; Dell’Oro et al, 2019 ; Laurin et al, 2017 ). Supplementary Figure S1 shows similar results for the NNP group in terms of BP.…”
Section: Resultsmentioning
confidence: 99%
“…The study of the pathophysiological mechanisms behind arterial hypertension in pregnant women and the physiological changes that pregnancy entails have been widely discussed over the years. While most of these studies focus on analyzing cardiovascular and nervous variables in terms of the magnitude of the effect of some stressors ( Park et al, 2018 ; Dell’Oro et al, 2019 ; Laurin et al, 2017 ; Wehrwein and Joyner, 2013 ; Marchi et al, 2015 ; Béchir et al, 2003 ), the present study focused on studying the dynamics of the interactions between the cardiovascular, respiratory, and nervous systems through wavelet phase coherence analysis. The results showed that in the HF band: i) normotensive pregnant women have a higher coupling between MSNA and respiration at rest than normotensive non-pregnant women; ii) normotensive pregnant women have a higher coupling of MSNA-RR and MSNA-BP than normotensive non-pregnant women at rest; iii) hypertensive pregnant women have a lower coupling of MSNA-RR and MSNA-BP than normotensive pregnant women during CPT.…”
Section: Discussionmentioning
confidence: 99%